Keefektifan Patogenesitas Steirmema Carpocapsae (all strain) terhadap Hama Plutella xylostella L. - Mariyono Mariyono; Eko Yuliarsha Sidhi; Nugraheni Hadiyanti (Kadiri University, 2021)
The utilization of entomopathogenic nematodes is an example of the uses of an environmentally friendly biological agent. Entomopathogenic nematodes of the family Steinernematidae and Hetrorhabditidae are very potential to control insect pests. The purpose of this study was to study the pathogenicity of the entomopathogenic nematode Steinernema carpocapsae (all strains) as a biological control against Plutella xylostella. This research includes 2 stages, namely the preparation stage and laboratory experiments. The experimental design in this study was a completely randomized design (CRD) consisting of six treatments and three replications. The treatments tested were entomopathogenic nematode concentrations consisting of six levels: 0, 8, 16, 32, 64 and 128 infective juvenile per ml. The LC50 and LT50 values were calculated using Probit analysis. The results of observations of nematodes that enter the insect body and pest mortality were analyzed using analysis of variance (ANOVA), once showing a significant difference, it was then continued to the DMRT test at 5% level. Based on the results of the study, the highest pathogenicity against Plutella xylostella was Steinernema carpocapsae (all strains) when compared to Steinernema glaseri (NC) and Steinernema sp. local isolates. Resistance to Steinernema carpocapsae (all strains) and the LC50 value were determined by the age of Plutella xylostella larvae. The bigger and older the larvae, the more its resistance to Steinernema carpocapsae (All strains) and the LC50 value. The number of entomopathogenic nematodes that enter the body of Plutella xylostella increased with increasing length of contact time.Penggunaan nematoda entomopatogen merupakan salah satu pemanfaatan agensia hayati yang ramah lingkungan. Nematoda entomopatogen dari famili Steinernematidae dan Hetrorhabditidae sangat potensial untuk mengendalikan serangga hama. Tujuan dari penelitian ini adalah mempelajari patogenisitas nematoda entomopatogen Steinernema carpocapsae (all strain) sebagai pengendali hayati terhadap hama Plutella xylostella. Penelitian ini meliputi 2 tahap yaitu tahap persiapan dan percobaan laboratorium. Rancangan percobaan pada penelitian ini adalah Rancangan Acak Lengkap (RAL) yang terdiri enam perlakuan dan tiga ulangan. Perlakuan yang diujikan adalah konsentrasi nematoda entomopatogen yang terdiri enam taraf: 0, 8, 16, 32, 64 dan 128 infektif juvenile/ml. Nilai LC50 dan LT50 dihitung menggunakan analisis probit. Hasil pengamatan nematoda yang masuk dalam tubuh serangga dan mortalitas hama dianalisis menggunakan analisis sidik ragam (ANOVA), apabila menunjukkan beda nyata dilanjutkan uji DMRT taraf 5%. Berdasarkan hasil penelitian, patogenisitas tertinggi terhadap Plutella xylostella adalah Steinernema carpocapsae (all strain) bila dibandingkan dengan Steinernema glaseri (NC) dan Steinernema sp. isolat lokal. Ketahanan terhadap Steinernema carpocapsae (All strain) dan nilai LC50 ditentukan umur larva Plutella xylostella. Semakin besar dan tua umur larva, ketahanan terhadap Steinernema carpocapsae (All strain) dan nilai LC50 juga semakin meningkat. Jumlah nematoda entomopatogen yang masuk kedalam tubuh Plutella xylostella semakin banyak seiring dengan bertambah lamanya waktu kontak.